Lemon grass cultivation for enhancing farmer’s income - Singh, Raghwendra; Yadav, Seema; Singh, S K; Dubey, S K (Indian Farming, 2024)
The rising human health consciousness has led to the use of side effect free natural product based molecule such as Lemon grass. The multiple uses of this aromatic plant such as pharmaceutical, perfumery, soap industry etc. has increased its demand in domestic as well international market, which has also paved the pathway of enhanced income and livelihood generation among Indian farmers. Moreover, cultivation of Lemon grass played an important role in livelihood security of tribal women. Cultivation of aromatic plants needs less input as compared to paddy cultivation as they can be grown with rain water and farmyard manure. For Indian farmer, Lemon grass cultivation is like gold earned from barren land and it also made many farm women socially empowered. KVK-Amroha has played an important role in enhancing production of Lemon grass and increased adoption rate of its farming by technology dissemination using high-yielding variety Krishna among Lemon grass cultivators.